2019
DOI: 10.1021/acsami.8b20025
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-Ion Intercalation into Graphite in SO2-Based Inorganic Electrolyte toward High-Rate-Capable and Safe Lithium-Ion Batteries

Abstract: Herein, we have identified that lithium ions in an SO 2 -based inorganic electrolyte reversibly intercalate and deintercalate into/out of graphite electrode using ex situ X-ray diffraction and various electrochemical methods. X-ray photoelectron spectroscopy shows that the solid electrolyte interphase on the graphite electrode is mainly composed of inorganic compounds, such as LiCl and lithium sulfur-oxy compounds. Graphite electrode in SO 2 -based inorganic electrolyte has stable capacity retention up to 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Currently, high-rate capabilities (not only high power but also fast charging) and low-temperature cold-cranking performances of LIBs have grown in importance for advancing EV performances. However, the requirements are still not fulfilled because of the high internal resistance of the cells. It has been regarded that the internal resistance is mainly attributed to the properties of the solid electrolyte interphase (SEI), especially generated at the graphite electrode. ,, Graphite has been commonly used as a negative electrode material for LIBs owing to its favorable properties, such as low working voltage (below 0.3 V vs. Li/Li + ) and reliable cycle performance. However, in the low-potential region, vigorous decomposition of carbonate-based electrolyte solutions occurs on the electrode surface due to their limited cathodic electrochemical stability window. Further decomposition of the electrolyte solution is yet suppressed by the formation of a SEI that enables repeated charge/discharge reactions in the following cycles. The SEI should be a facile Li-ion conductor and mechanochemically stable with a thin and compact structure. Otherwise, further electrolyte decomposition occurs during cycling and increases the interphasial impedance and consumes confined Li-ions in cells, leading to poor rate capability and capacity fading of LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, high-rate capabilities (not only high power but also fast charging) and low-temperature cold-cranking performances of LIBs have grown in importance for advancing EV performances. However, the requirements are still not fulfilled because of the high internal resistance of the cells. It has been regarded that the internal resistance is mainly attributed to the properties of the solid electrolyte interphase (SEI), especially generated at the graphite electrode. ,, Graphite has been commonly used as a negative electrode material for LIBs owing to its favorable properties, such as low working voltage (below 0.3 V vs. Li/Li + ) and reliable cycle performance. However, in the low-potential region, vigorous decomposition of carbonate-based electrolyte solutions occurs on the electrode surface due to their limited cathodic electrochemical stability window. Further decomposition of the electrolyte solution is yet suppressed by the formation of a SEI that enables repeated charge/discharge reactions in the following cycles. The SEI should be a facile Li-ion conductor and mechanochemically stable with a thin and compact structure. Otherwise, further electrolyte decomposition occurs during cycling and increases the interphasial impedance and consumes confined Li-ions in cells, leading to poor rate capability and capacity fading of LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of LGEs in safe LIBs include flame retardant fluorinated alkane, 147–149 nonflammable SO 2 (ref. 56 and 150 ), NH 3 , 57 etc. Yin et al 148 demonstrated a fire-extinguishing liquefied gas electrolyte based on 1,1,1,2-tetrafluoroethane (TFE) and pentafluoroethane (PFE) with a high Fp (TFE, 250 °C) and high ionic conductivity (>3 mS cm −1 from −78 to 80 °C, Fig.…”
Section: Principles and The Design Strategies Of Nonflammable Electro...mentioning
confidence: 99%
“…8). 80 By means of XPS it was determined that the SEI was mainly composed of the inorganic reduction products of the SO 2 -based inorganic electrolyte such as lithium chloride, lithium sulfide, lithium oxide, and lithium sulfur-oxy compounds. The remarkable electrochemical performance was attributed to the high conductivity and formation of a highly efficient SEI layer.…”
Section: Inorganic Liquid Electrolytes (Ies)mentioning
confidence: 99%
“…The remarkable electrochemical performance was attributed to the high conductivity and formation of a highly efficient SEI layer. 80 An ammonia-based (NaYÁxNH 3 ) electrolyte is a promising alternative route towards safe, cheap, fast-charging and highpower SIBs. 81 This type of electrolyte has the distinctive feature of being non-flammable (although having high volatility), high Na + concentration (7 M), and high ionic conductivity (65-105 mS cm À1 ).…”
Section: Inorganic Liquid Electrolytes (Ies)mentioning
confidence: 99%